Magnetic poly(β-cyclodextrin-ionic liquid) nanocomposites for micro-solid phase extraction of selected polycyclic aromatic hydrocarbons in rice samples prior to GC-FID analysis - Boon, Yih Hui; Zain, Nur Nadhirah Mohamad; Mohamad, Sharifah; Osman, Hasnah; Raoov, Muggundha (Elsevier, 2019)
Poly(β-cyclodextrin functionalized ionic liquid) immobilized magnetic nanoparticles (Fe3O4@βCD-Vinyl-TDI) as sorbent in magnetic µ-SPE was developed for the determination of selected polycyclic aromatic hydrocarbons (PAHs) in rice samples coupled with gas chromatographic-flame ionization detector (GC-FID). The nanocomposite was characterized by various tools and significant parameters that affected the extraction efficiency of PAHs were investigated. The calibration curves were linear for the concentration ranging between 0.1 and 500 μg kg−1 with correlation determinations (R2) from 0.9970 to 0.9982 for all analytes. Detection limits ranged at 0.01–0.18 μg kg−1 in real matrix. The RSD values ranged at 2.95%–5.34% (intra-day) and 4.37%–7.05% (inter-day) precision for six varied days. The sorbents showed satisfactory reproducibility in 2.9% to 9.9% range and acceptable recovery values at 80.4%–112.4% were obtained for the real sample analysis. The optimized method was successfully applied to access content safety of selected PAHs for 24 kinds of commercial rice available in Malaysia.